Secondary tuberculosis of adjacent segments after anterior cervical discectomy and fusion: A case report - Liu, Chengjiang; Liu, Yidong; Ma, Boyuan; Zhou, Mengmeng; Zhao, Xinyan; Fu, Xuanhao; Kan, Shunli; Hu, Wei; Zhu, Rusen (Frontiers in Surgery, 2023)
Introduction Anterior cervical discectomy and fusion (ACDF) is a common operation for spinal surgery to treat a variety of cervical diseases. The postoperative infection rate of this procedure is extremely low, and adjacent segments are rarely involved. Tuberculosis (TB) is a common infectious disease that affects the spine in less than 1% of cases and is more common in the thoracolumbar and rarely cervical spine. Herein, for the first time, we report tuberculosis infection in adjacent segments after ACDF. Case presentation We report a 50-year-old patient with cervical spondylotic myelopathy (CSM) who was discharged from the hospital after receiving ACDF at the C3/4 level. Two months later, he was admitted to the hospital with neck pain and found to be infected with tuberculosis in C4/5. After 4 months of anti-tuberculosis treatment, the vertebral body was fused. Conclusion After ACDF, the adjacent cervical vertebrae were infected with TB but the infection was limited. We believe that the special vertebral blood supply and postoperative secondary blood-borne infection may lead to the occurrence of extrapulmonary tuberculosis.